Effects of Rumensin® ruminal delivery devices in grazing cattle on subsequent feedlot performance - Riley, Jack G.; Cochran, B.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Rumensin® Ruminal Delivery Devices put in place 76 days prior to steers entering a feedlot resulted in an average reduction in daily dry matter intake of 3.6% and a small 1.8% increase in daily gain during a controlled 28-day feeding phase. All steers were fed an 85% concentrate feedlot diet fortified with 30g/ton of Rumensin® and 10 g/ton of tylan®.
Keywords: Beef; Rumensin®; Ruminal; Feedlot performance